A New Multilevel Inverter with Reduced Number of Switches - Gnana Prakash; Balamurugan M; Umashankar S (Institute of Advanced Engineering and Science, 2014)
In recent day’s Multilevel inverter (MLI) technologies become a incredibly main choice in the area of high power medium voltage energy control. Though multilevel inverter has a number of advantages it has drawbacks in the vein of higher levels because of using more number of semiconductor switches. This may leads to vast size and price of the inverter is very high. So in order to overcome this problem the new multilevel inverter is proposed with reduced number of switches. The proposed method is well suited for a high power application and it built with three Dc sources and six Switches. Multi carrier pwm technique is used for sine wave generation. The results are validated through the harmonic spectrum of the FFT window by using Matlab/simulink. The result of the proposed MLI is compared with the conventional MLI and other seven level existing topologies.DOI: http://dx.doi.org/10.11591/ijpeds.v5i1.6089